Note—Prediction Intervals for Warranty Reserves and Cash Flows - Patankar, Jayprakash G.; Worm, George H. (Management Science, 1981)
This paper presents estimates of cash flows associated with a given warranty policy. Included in the results are prediction intervals for warranty reserves and cash flows. A numerical example is given to illustrate these results.